2020
DOI: 10.1177/0363546520971749
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Frequency and Severity of Postoperative Pain After Arthroscopic Rotator Cuff Repair Surgery

Abstract: Background: Postoperative pain after arthroscopic rotator cuff repair (RCR) is difficult to predict and manage. The experience of pain is thought to be influenced by a range of different factors. Determining which patient factors contribute to the pain may help us to better understand and manage it. Purpose: To evaluate the preoperative patient characteristics that may be predictive of, and correlated with, postoperative pain after arthroscopic RCR. Study Design: Cohort study; Level of evidence, 3. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Recent literature has shown that preoperative pain is a strong predictor for postoperative pain following RCR. 20 This study also suggested that alongside the association of severity and frequency of preoperative pain with postoperative pain, other factors such as smaller tear size, young age, female sex, and worker’s compensation status were associated with 6-week postoperative pain after RCR. 20 Leroux et al.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Recent literature has shown that preoperative pain is a strong predictor for postoperative pain following RCR. 20 This study also suggested that alongside the association of severity and frequency of preoperative pain with postoperative pain, other factors such as smaller tear size, young age, female sex, and worker’s compensation status were associated with 6-week postoperative pain after RCR. 20 Leroux et al.…”
Section: Discussionmentioning
confidence: 62%
“… 20 This study also suggested that alongside the association of severity and frequency of preoperative pain with postoperative pain, other factors such as smaller tear size, young age, female sex, and worker’s compensation status were associated with 6-week postoperative pain after RCR. 20 Leroux et al. 21 reviewed 79,287 patients who underwent elective shoulder surgery and found that history of alcohol abuse, depression, or anxiety and female sex all had the most significant influence on risk of developing long-term opioid use.…”
Section: Discussionmentioning
confidence: 62%
“…Although older individuals are at increased risk of degenerative conditions, such as arthritis and rotator cuff disease, younger patients report increased pain following rotator cuff repair surgery. 6 Younger age is also a significant risk factor for graft failure following anterior cruciate ligament (ACL) reconstruction. 7 Although further research is needed to better explain the reason for these differences, it is clear that sex and age are important determinants of the burden of musculoskeletal (MSK) disease, as well as the response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic rotator cuff repair is becoming the main surgical method. Despite being characterized as a “minimally invasive” procedure, arthroscopic rotator cuff repair is associated with significant postoperative pain in the acute perioperative period 2. Opioids are commonly used for postoperative pain reduction; however, their use is associated with adverse effects (AEs) and should be limited 3.…”
mentioning
confidence: 99%
“…Despite being characterized as a "minimally invasive" procedure, arthroscopic rotator cuff repair is associated with significant postoperative pain in the acute perioperative period. 2 Opioids are commonly used for postoperative pain reduction; however, their use is associated with adverse effects (AEs) and should be limited. 3 Therefore, multimodal analgesia has been introduced to reduce postoperative pain and side effects during the use of postoperative opioids.…”
mentioning
confidence: 99%